The uniqueness of Jesus Christ and singularity of Christianity in front of religious pluralism - Bara Bancel, Silvia (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
The Second Vatican Council displayed a change in the Catholic Church’s attitude towards other religions. Subsequent theological reflection on inter-religious dialogue has given different answers to questions about the value of non Christian religions and the meaning of Christianity’s claim for truth and singularity. One of the authors that has recently developed these issues is the Dominican Claude Geffré. His proposals, though original and inspiring, are presented in a fragmentary way in what he has published to date. In this paper, a methodical and orderly presentation of his theology is presented; his intellectual debts to other authors are exposed; and, at the end, a critical evaluation of his theology is undertaken.